Diferencias individuales y rendimiento académico en estudiantes de bachillerato, asignatura matemática de la Unidad Educativa "Chibuleo", periodo 2021 – 2022. - Quishpe Cuvi, María Piedad (2022)
Individual differences in learning make up components that enhance, facilitate, or hinder the students learning process, advantages and disadvantages that interfere in the academic performance of students, where relevant components of student's personality, the cognitive constructions formation, abilities, styles and learning tactics are involved. However, it is a real problem to adapt the scientific training and critical thinking demands. Therefore, understand and comprehend, the student´sindividual differences or group that are exclusive, the teacher needs to adapt teaching strategies according to the student's own way or learning styles, necessary to improve their capacities and develop their potential. This research explains how individual differences are related to academic performance through Felder and Silverman's learning styles it means the quantitative approach to observe the complexity and nature of the problem while the research type is field and cross sectional by its temporality. The index of learning styles questionnaire was used, which defines learning styles in four dimensions, with results of each student and each group presents their own ways of learning oriented especially to the visual, sequential, active and sensory way, so that individual differences and the way of learning affects the student's academic performance.